Bilateral Idiopathic Neuroretinitis - Cosmin Adrian Teodoru; Horațiu Dura; Mihai Dan Roman; Adrian Hașegan; Ciprian Tănăsescu; Andrei Moisin; Doina Ileana Giurgiu; Mihaela Laura Vică; Horia Stanca; Maria-Emilia Cerghedean-Florea; Corina Suteu (Diagnostics)
Background/Objectives: Neuroretinitis (NR) is a rare inflammatory condition characterized by sudden vision loss, optic disc edema and macular star appearance predominantly affecting individuals in their third and fourth decades of life. Methods: This paper describes the case of 33-year-old Caucasian man with no significant medical history complaining of decreased vision for about a week. Results: The ophthalmological exam revealed best-corrected visual acuity (BCVA) for the right eye (RE) of 0.8 (decimal notation) and of 0.9 for the left eye (LE). Intraocular pressure (IOP) was 20 mmHg in RE and 18 mmHg in LE. Slit-lamp examination of both eyes (OU) showed no evidence of intraocular inflammation in the anterior chamber or vitreous cavity. Examination of the posterior pole of the right eye showed bilateral papilledema with an incomplete macular fan pattern. Conclusions: Despite extensive laboratory tests, including serologic and imaging investigations, a definitive etiology remained unclear. It is very important to differentiate NR from other optic nerve disorders, requiring careful clinical evaluation and observation of the evolution of symptoms.